STUDI SOSIAL EKONOMI MASYARAKAT PASCA LONGSOR DI KENAGARIAN TANDIKEK KECAMATAN PATAMUAN KABUPATEN PADANG PARIAMAN - Oktalia, Mitra; Juita, Erna; Iswandi U, Iswandi U (STKIP PGRI Sumbar, 2013)
The purpose of this study that is to describe the data about study : (1) Level of education of post-landslide in Kenagarian Tandikek District Patamuan Padang Pariaman district. (2) Condition of social live place Kenagarian Tandikek district Patamuan Padang Pariaman Padang Pariaman district. (3) Level ofÂ social income of post landslide in Kenagarian Tandikek district Patamuan Padang Pariaman district. This research is a descriptive study and the sample in this study amounted to 864 households taken using the Proportional random sampling technique with a proportion of 10%, so the sample size is 86 KK.Â Instrument in the form of a questionnaire study. The study get information that: (1) leveloof the childs education level of education after landslide in Kenagarian Tandikek District Patamuan Padang Pariaman district in general society son graduated from high school while experiencing failure at the level of post-avalanche education average in junior high (2) the living conditions of post landslides in Kenagarian Tandikek District Patamuan Padang Pariaman district generally has a permanent home with a spacious 36 M2 (3) The condition of side income communities Kenagarian Tandikek Post landslide in Padang Pariaman District Patamuan district average of Rp 50,000-100,000 day.